Effect of different BAP and TDZ concentration on shoot multiplication from shoot tip explant of Dianthus caryophyllus - Zainal Abdidin, Maryam Shakirah (2014)
Dianthus caryophyllus is known as carnation or bunga teluki. It is a monoecious perennial plant. In Malaysia, carnation is used as cut flower for many occasions and events. Seeds of carnation can produce virus free plant. However, one seed can only generate one plant. To produce mass numbers of virus free carnation plants, propagating carnation through in-vitro could be an alternative approach by the growers. Besides that, in-vitro culture technique reduces the spaces needed for micropropagating the plants and also plants can be produced within a shorter period of time. The objective of this study is to determine the best BAP and TDZ concentration in inducing shoot proliferation from shoot tip explant of carnation. The explant used is shoot tip excised from 12 days old germinated seedling of dianthus caryophyllus. This explants are cultured in Murashige and Skoog (1962) medium supplemented with 6-benzylaminopurine (BAP) at concentrations of 0.5, 1, 2, and 5 mg/L and Thidiazuron (TDZ) at 0.02, 0.09, 0.22, and 1.1 mg/L. It is observed that there is an inconsistent trend in shoot multiplication with increasing BAP and TDZ concentrations. The highest mean number of shoots formed per explant was observed in medium supplemented with1.1 mg/L TDZ. It is also observed that the medium without cytokinin (control treatment) also induced shoot multiplication indicating that endogenous hormone might have triggered the shoot induction.